2017
DOI: 10.1136/bmjopen-2017-016689
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking exercise identity: a qualitative study of physically inactive cancer patients’ transforming process while undergoing chemotherapy

Abstract: ObjectiveTo explore physically inactive breast and colon cancer patients’ prediagnosis exercise history and attitudes to physical activity (PA) and experiences in initiating PA while undergoing adjuvant chemotherapy.DesignAn explorative qualitative study guided the interpretive analysis of semistructured, open-ended interviews conducted at initiation of chemotherapy and after 12 weeks. The study was embedded in a pilot randomised controlled trial.SettingParticipants were recruited from the Oncological Departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(69 citation statements)
references
References 40 publications
2
67
0
Order By: Relevance
“…This network helps patients in understanding information, provides support and manages overall care that patients would otherwise not receive from their HCPs [28]. Most patients start and continue to do physical activities due to the emotional and practical support of their social network [30,31]. One should note that physical activity is still rarely a topic in daily clinical practice and patients may seek support from their social network.…”
Section: Discussionmentioning
confidence: 99%
“…This network helps patients in understanding information, provides support and manages overall care that patients would otherwise not receive from their HCPs [28]. Most patients start and continue to do physical activities due to the emotional and practical support of their social network [30,31]. One should note that physical activity is still rarely a topic in daily clinical practice and patients may seek support from their social network.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in both interventions received individual test feedback and health counselling and symptom guidance at baseline and at weeks 6, 12 and 39 to help counteract barriers and to support individual motivational aspects to initiate and prioritise leisure time PA 27,38 . The theoretical framework for initiating and adopting behavioural change at onset and during adjuvant chemotherapy focused on recognising pre-exercise history, individual goal planning, family resources and the immediate pitfalls during anticancer treatment as crucial determinants for the individual to rethink regular exercise as pivotal for their health and post-cancer life priorities 36 .…”
Section: Instructed Pedometer Intervention Individual 12-week Instrumentioning
confidence: 99%
“…The questions for future research on the social challenges as a side effect of cancer and the social benefits illuminated in this study and other literature involve whether the family or close relatives of cancer patients should be included in the shared community explored in the present study. A study by Adamsen et al () described how relatives of patients with breast cancer or prostate cancer were included in a physical activity intervention, which helped strengthen the relationship between the participating relatives and the patients as a basis for their shared social life. Research is required to explore the potential social benefits or challenges of including relatives in programmes facilitating human interaction and sharing of illness experiences.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also reported how the relationship might be ambiguous (Andersen, Larsen, & Birkelund, ; Birkelund & Larsen, ; Borregaard & Ludvigsen, ; Larsen, Larsen, & Birkelund, ). Studies on exercise for patients with cancer have also reported social benefits of participating in group‐based interventions (Adamsen, Andersen, Lillelund, Bloomquist, & Moller, ; Backman, Browall, Sundberg, & Wengstrom, ; Missel et al, b); however, the meaning of participating in group‐based exercise for patients after lung cancer surgery is sparsely investigated. The objective of this qualitative study was to explore the lived experiences and social benefits among patients with operable NSCLC who participated in an exercise programme.…”
Section: Introductionmentioning
confidence: 99%